SISTEM INFORMASI BPHTB (BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN) KAB. MUARO JAMBI: BPHTB, TAX, PHP PROGRAMING LANGUAGE, INFORMATION SYSTEM - Tamrinsyah (LP2M STMIK Nurdin Hamzah Jambi, 2017)
BPHTB or duty on the acquisition of land and building rights are taxes imposed on the acquisition of land and building rights. Acquisition of rights to land and buildings is a legal act or event resulting in the acquisition or possession of rights to land and buildings by private individuals or entities. The purpose of this research is to know the process that occurred at BPHTB Kab. Muaro Jambi. The method used in this research is quantitative descriptive method with data acquisition technique that is survey, interview, documentation and literature study. The results obtained in the analysis then used as a reference in the design and construction BPHTB application Kab. Muaro Jambi web-based. Contribution generated from the built program is expected to create administration BPHTB Kab. Muaro Jambi is regular and compatible so it can increase local revenue